3D Printing of BaTiO3/PVDF Composites with Electric In Situ Poling for Pressure Sensor Applications. Issue 11 (23rd August 2017) - Kim, Hoejin; Torres, Fernando; Villagran, Dino; Stewart, Calvin; Lin, Yirong; Tseng, Tzu‐Liang Bill
Abstract: This paper presents 3D printing of piezoelectric sensors using BaTiO3 (BTO) filler in a poly(vinylidene) fluoride (PVDF) matrix through electric in situ poling during the 3D printing process. Several conventional methods require complicated and time‐consuming procedures. Recently developed electric poling‐assisted additive manufacturing (EPAM) process paves the way for printing of piezoelectric filaments by incorporating polarizing processes that include mechanical stretching, heat press, and electric field poling simultaneously. However, this process is limited to fabrication of a single PVDF layer and quantitative material characterizations such as piezoelectric coefficient and β‐phase percentage are not investigated. In this paper, an enhanced EPAM process is proposed that applies a higher electric field during 3D printing. To further increase piezoelectric response, BTO ceramic filler is used in the PVDF matrix. It is found that a 55.91% PVDF β‐phase content is nucleated at 15 wt% of BTO. The output current and β‐phase content gradually increase as the BTO weight percentage increases. Scanning electron microscopy analysis demonstrates that larger agglomerates are formulated as the increase of BTO filler contents and results in increase of toughness and decrease of tensile strength. The highest fatigue strength is observed at 3 wt% BTO and the fatigue strength gradually decreases as the BTO filler contents increases. Abstract : The fabrication of piezoelectric pressure sensors with BaTiO3 (BTO) nanoparticles in a poly(vinylidene) fluoride (PVDF) matrix through electric in situ poling during the FDM 3D printing process is presented. The enhanced electric poling‐assisted additive manufacturing process enables to polarize dipoles of PVDF and BTO to longitudinal direction.